The swimmer's otitis. An up to date and prevention options - G. Caramia; V. Serafini; A. Loggi (PAGEPress Publications, 2013)
The swimmer's otitis or acute otitis externa, is a pathology that often occurs in those who practice swimming at a competitive level. The same problem often occurs in the summer with the attendance of swimming pools and bathing areas. A survey made in the United States in 2007 confirms the dynamics of the onset of this pathology, because the contamination of fungi and bacteria in the waters of the swimming pools and the sea cause the inflammation of the epithelium of the auditory canal. To face this issue, in addition to a correct diagnosis, and the necessary and appropriate therapies, it may follow the use of these medicinal preparations. The first one (A) is protective-acting, the second one (B) is characterized as a preventive, hygroscopic, moistening, antiseptic and antimycotic-acting solution. Swimmers who have been using the two (pre-and post) preparations daily for about a year have reported sporadic episodes of otitis. However, there is no doubt that these two compounds deserve a meticulous clinical trial in order to confirm their preventive and therapeutic potentials in external acute otitis.